2005
DOI: 10.1086/429990
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet to Mid‐Infrared Observations of Star‐forming Galaxies atz ∼ 2: Stellar Masses and Stellar Populations

Abstract: We present the broadband UV through mid-infrared spectral energy distributions (SEDs) of a sample of 72 spectroscopically confirmed star-forming galaxies at z ¼ 2:30 AE 0:3. Located in a 72 arcmin 2 field centered on the bright background QSO, HS 1700+643, these galaxies were preselected to lie at z $ 2 solely on the basis of their restframe UV colors and luminosities and should be representative of UV-selected samples at high redshift. In addition to deep ground-based photometry spanning from 0.35 to 2.15 m, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
603
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(649 citation statements)
references
References 52 publications
42
603
4
Order By: Relevance
“…From their optical and nearinfrared (NIR) studies, Finkelstein et al (2009) found a more robust dust-corrected and de-lensed SFR of 266 ± 74 M yr −1 . Their result confirms that this system is undergoing a very active process of star formation, and shows that the SFR is higher than ∼85% of the high redshift LBGs studied by Shapley et al (2001Shapley et al ( , 2005.…”
Section: Introductionsupporting
confidence: 54%
“…From their optical and nearinfrared (NIR) studies, Finkelstein et al (2009) found a more robust dust-corrected and de-lensed SFR of 266 ± 74 M yr −1 . Their result confirms that this system is undergoing a very active process of star formation, and shows that the SFR is higher than ∼85% of the high redshift LBGs studied by Shapley et al (2001Shapley et al ( , 2005.…”
Section: Introductionsupporting
confidence: 54%
“…The slope and scatter are expected to be a direct reflection of the similarity in the shape of galaxy SFHs among various models and at various masses (Davé 2008;Noeske et al 2007b). It is worth noting that other z = 2 observations suggest a somewhat large scatter (Shapley et al 2005;Papovich et al 2006), so the observational picture is not entirely settled. Figure 12 shows the SFR of each galaxy of our sample as a function of the corresponding M and the results of various models and observations: analytical models of Buat et al (2008) and Noeske et al (2007a), the semi-analytical Millennium simulations of Kitzbichler & White (2007) used in Buat et al (2008) and observations of Elbaz et al (2007), Daddi et al (2007), and Santini et al (2009).…”
Section: Star Formation Rate and Stellar Massmentioning
confidence: 98%
“…In contrast to the results of Gonzalez et al (2010) and Labbé et al (2010), our relatively young ages resemble those found by Verma et al (2007) and Yabe et al (2009) for z ∼ 5, which are younger than z ∼ 2−3 LBGs (cf. Shapley et al 2001Shapley et al , 2005Sawicki et al 2007;Yabe et al 2009). However, other studies (e.g., Stark et al 2007a;Eyles et al 2007;Stark et al 2009), find relatively old ages at z ∼ 6, and Yabe et al (2009) confirm some of them with their method.…”
Section: Comparison With Lower Redshift Galaxiesmentioning
confidence: 99%